Hysteroscopic management versus ultrasound-guided evacuation for women with first-trimester pregnancy loss, a randomised controlled trial - Hadeer Meshaal; Emad Salah; Eman Fawzy; Mazen Abdel-Rasheed; Ahmed Maged; Hany Saad (BMC, 2022)
Abstract Objective We aimed to evaluate the hysteroscopic management of first-trimester pregnancy loss compared to surgical evacuation either blind or under ultrasonographic guidance‎. Methods This clinical trial included ‎315 women with first-trimester pregnancy loss, divided equally into three groups. Group 1 underwent traditional blind surgical evacuation, group 2 underwent ultrasound-guided evacuation, and group 3 underwent hysteroscopic management. All women were assessed for retained products, surgical complications, the need for further management, and pregnancy occurrence after evacuation within 2 years of follow up. Results The rate of presence of conception remnants and the need for further ‎treatment was significantly higher in group 1 compared to groups 2 and 3 (4.8% vs. 0% vs. 0%, P = 0.012). The conception rate within 2 years was significantly lower in group 1 compared to groups 2 and 3 (57.4% vs. 73.2% vs. 82.7%, P = 0.002), and the duration needed to conceive was significantly prolonged in group 1 compared to groups 2 and 3 (9.8 vs. 8.3 vs. 6.9 months, P < 0.001). Interestingly, women who underwent hysteroscopic management needed a significantly shorter time to conceive than those who underwent ultrasound-guided evacuation‎ (6.9 vs. 8.3 months, P = 0.006). Conclusions Hysteroscopic management of first-trimester pregnancy loss was superior to ultrasound-guided surgical evacuation regarding the time interval to conceive. Both techniques were superior to the blind evacuation technique regarding removal of the whole conception remnants, need for further treatment and fertility outcomes. Clinical trial registration: It was first registered at ClinicalTrials.gov on 16/03/2017 with registration number NCT03081104.